2013
DOI: 10.3347/kjp.2013.51.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Toxocariasis by ELISA Using Crude Antigen of Toxocara canis Larvae

Abstract: Toxocariasis is a worldwide zoonosis caused by larvae of ascarid nematodes of dogs or cats, Toxocara canis or T. cati. Diagnosis of human toxocariasis currently relies on serology that uses T. canis excretory-secretory antigen to detect specific IgG antibodies by ELISA. We investigated the serodiagnostic efficacy of ELISA using crude antigen of T. canis larvae (TCLA). Serum specimens of 64 clinically confirmed toxocariasis, 115 healthy controls, and 119 other tissue-invading helminthiases were screened by ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 19 publications
5
67
0
Order By: Relevance
“…However, as documented cases of toxocariasis are rarely described in Norway, we would not expect our study participants to have specific IgE towards Toxocara spp. We therefore focused on assessing IgG4 towards Toxocara spp., which is most commonly used for serodiagnosis of toxocariasis . Although we did not have data on specific IgE towards Ascaris or Toxocara in the present study, we cannot exclude the possibility that exposure to HDM or cockroach allergens may have influenced A. lumbricoides IgG4 seropositivity as observed in the present study.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…However, as documented cases of toxocariasis are rarely described in Norway, we would not expect our study participants to have specific IgE towards Toxocara spp. We therefore focused on assessing IgG4 towards Toxocara spp., which is most commonly used for serodiagnosis of toxocariasis . Although we did not have data on specific IgE towards Ascaris or Toxocara in the present study, we cannot exclude the possibility that exposure to HDM or cockroach allergens may have influenced A. lumbricoides IgG4 seropositivity as observed in the present study.…”
Section: Discussionmentioning
confidence: 56%
“…We therefore focused on assessing IgG4 towards Toxocara spp., which is most commonly used for serodiagnosis of toxocariasis. 57 Although we did not have data on specific IgE towards Ascaris or Toxocara in the present study, we cannot exclude the possibility that exposure to HDM or cockroach allergens may have influenced A. lumbricoides IgG4 seropositivity as observed in the present study. However, we did not observe any association between Ascaris or Toxocara IgG4 and allergic sensitization (SPT or specific IgE) towards HDM, which is the most commonly described cross-reactive allergen with helminths.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…For example, Lim and his colleagues [26] suggested that toxocariasis is common but neglected by doctors mostly due to their lack of awareness. The second, toxocariasis is unaware to doctors and abandoned by lack of good routine diagnostic service in many regions [27]. The seroprevalence of anti- Toxocara antibodies was not significantly associated with the prior history of contact with dogs, consumption of unwashed fruits and vegetables, or use of cattle/sheep liver (P>0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The ELISA (Biokema-Affinity Products, Crissier-Lausanne, Switzerland) [28] at a serum titer greater than 1: 32 has 78% sensitivity for the detection of toxocariasis [29] and Hagler et al [30] suggested that a serum titer of 1: 8 is sufficient to support a diagnosis of ocular toxocariasis if the patient has signs and symptoms compatible with that disorder. In addition to the commercial ELISA kit, serodiagnosis by ELISA using crude antigen of toxocara larvae developed by researchers in Seoul National University in South Korea also showed acceptable diagnostic value with 92.2% sensitivity and 86.6% specificity [31]. It has been reported that recombinant antigens [32] can offer further solutions for serologic diagnosis by providing increased sensitivity and specificity compared to native excretory-secretory antigens.…”
Section: Diagnosismentioning
confidence: 99%